Fae stickjoy & deco / Farah Hanis Mustafa ... [et al.] - Mustafa, Farah Hanis; Mohd Wahid, Muhammad Azim; Yusof, Mohamad Akmal; Muhammad Tahir, Amirul Ariff; Mohd Hanif, Nor Efazira (2021)
This business is based on partnership where it consists of five partners. The business capital is amounted to RM 6,000 where the total contribution of each member is RM 30,000 and the rest RM 13,619 is from MARA's loan and RM 8000 of van's price as hire-purchase. With loan given as a support from MARA , we are hoping that FAE STICKJOY & DECO is able to achieve outstanding demand from consumer. Our business is supplying wallcovering from company which processes the wallpaper and we sell it and at the same time we give the best services to customers. This kind of business is known as trading. We know that trading business type still can be run by one person, but we need our partners to install the wallpaper at customer's house, consult on design of wallpaper with their room. Before we start our business on Ji.me 2017, we will go to business seminar and wallpaper class to gain our knowledge, so that , we know the path of the business even we are new in this region. A t wallpaper class, they will teach on how to choose wallpaper based on size of the room, furniture, light and etc. They will also teach how to install and remove the wallpaper so that the wall do not damage. The partners get income payment as total of each contribution to start the business, better than if we hire a worker to install wallpaper, they get their payment but they do not contribute any equity , at this situation, we can save the cost and get profit on that. Wallpaper's category that most popular in our company is English Floral , Modern and Korean style. We are aiming on Malay customer to choose our company because our competitors have high possibilities will be all Chinese company. So, we hope our own Malay people could support us and at the same time we can help our Malay people to be successful.